Association of serum 25-hydroxyvitamin D concentrations with all-cause mortality among individuals with kidney stone disease: the NHANES database prospective cohort study - Gao, Meng; Liu, Minghui; Chen, Jinbo; Zhu, Zewu; Chen, Hequn (Frontiers in Endocrinology, 2023)
The purpose of this study was to investigate the correlation between serum 25(OH)D concentrations and all-cause mortality in patients with kidney stone disease (KSD), as the effects of a deficiency in 25-hydroxyvitamin D on KSD patients are currently unclear.Methods: For our prospective cohort study, we included 2,916 participants from the National Health and Nutrition Examination Survey (NHANES) 2007-2018. The National Death Index (NDI) was utilized to identify all causes of death and cause-specific mortality until December 31, 2018. We calculated hazard ratios (HR) and 95% confidence intervals (CIs) using multivariate Cox regression models.Results: During the 18,859 person-years of follow-up, a total of 375 fatalities occurred, including 83 deaths from cardiovascular disease (CVD) and 79 deaths from cancer. At baseline, individuals with higher blood 25(OH)D concentrations had lower levels of glucose, glycohemoglobin, CRP, and insulin, as well as higher levels of HDL cholesterol (P < 0.01). In the fully adjusted model (Model 3), compared to the group with the lowest 25(OH)D concentrations, those with serum 25(OH)D concentrations ≥ 75 nmol/L had hazard ratios (HRs) and 95% confidence intervals (CIs) of 0.48 (0.26, 0.87) for allcause mortality (P=0.02, P for trend = 0.02). The association between serum 25(OH)D concentrations and all-cause mortality in KSD patients was found to be significantly non-linear. A 7% decrease in the risk of death from all causes was observed for each unit-nmol/L increase in serum 25(OH)D concentrations when the concentrations were below 27.7 nmol/L (P < 0.05).Conclusions: Based on the findings, KSD patients with insufficient serum 25(OH)D concentrations were at a higher risk of all-cause mortality. Therefore, it is crucial to maintain sufficient blood 25(OH)D concentrations and prevent 25(OH)D insufficiency in order to extend the lifespan of KSD patients.